2009
DOI: 10.1002/ccd.21967
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery stent fracture with refractory hypertension: A case report and review of the literature

Abstract: A 73-year-old man with resistant hypertension and impaired renal function underwent stenting for right renal artery (RRA) stenosis. Two years later, he presented with uncontrolled hypertension and worse renal function. Renal arteriogram revealed RRA stent fracture with in-stent restenosis. Another stent was deployed. Four months later, however, renal arteriogram revealed in-stent restenosis again. This time, balloon angioplasty alone was performed. He had been symptom-free with stable condition at 2-year follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In cases, angioplasty had been reported as very useful, but other authors have reported poor long-term results needing the use of stents [1,[10][11][12][13][14][15]. In our patient, the angioplasties performed obtained an excellent immediate result, but really poor intermediate or long-term results.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In cases, angioplasty had been reported as very useful, but other authors have reported poor long-term results needing the use of stents [1,[10][11][12][13][14][15]. In our patient, the angioplasties performed obtained an excellent immediate result, but really poor intermediate or long-term results.…”
Section: Discussionmentioning
confidence: 44%
“…Fracture of stents have been reported by other authors as well, [14,15] although there have been only a few reports of stent fractures in the renal arteries. Chua and Hung [15] suggested as the renal artery entrapment by the diaphragmatic crus, and a mobile kidney with an acute angulation at the proximal segment of the renal artery, as the 2 possible reasons for stent fracture. The reason mentioned by Guzzetta and his co-workers, [16] also dealt with the motion of the renal artery.…”
Section: Discussionmentioning
confidence: 90%
“…This bending may lead to stent fracture and restenosis [14]. An alternative is to treat with balloon angioplasty and cutting balloon angioplasty, which may have lower patency rate but fewer stent-related complications in these patients [15]. …”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Not surprisingly, balloon angioplasty failed in these cases due to elastic recoil, and stenting failed due to bending and fracture of the implanted stent. [9][10][11]13 Since renal artery entrapment has an extrinsic etiology, we strongly suggest to also treat it from outside of the renal artery.…”
Section: Discussionmentioning
confidence: 99%